Bahasa Inggris - Valisneria Utami (Universitas Putera Batam, 2020)
Many research concerning pronunciation problems of Chinese learners majorly take place within the country, yet very few of them conducted in the context where English is the native language of the country. This study aims to explore the problematic features of pronunciation of Chinese student who studied in Australian university. This study employs qualitative approach with a single case study. The data were collected through an interview and two models of speaking; monologue and reading a text. The problematic features, then, were prioritized based on its context and concept of English as International Language (EIL) context proposed by Jennifer Jenkins (2006). The result showed that the participant was aware about her pronunciation issues. Several problematic segmental and suprasegmental features in which emerged during data analysis also supported this finding. The problematic features are consonant cluster, long and short vowels, /r/ and /l/ sounds, schwa addition in monosyllabic words, /æ/, /ɛ/ and /ʌ/, and issues in word stress, prominence, and intonation. Among all these features, the proposed prioritization of teaching is to focus on word stress, consonant cluster, intonation and prominence, /r/ and/l/, and long and short vowels. The findings also showed slightly difference in which in this study, the participant did not encountered difficulties in pronouncing double /l/ sounds.This study concludes with recommendation for teaching and learning these problematic features.